2017
DOI: 10.1136/bmjoq-2017-000060
|View full text |Cite
|
Sign up to set email alerts
|

Transition from a dedicated to a non-dedicated, ward-based pharmacist antimicrobial stewardship programme model in a non-academic hospital and its impact on length of stay of patients admitted with pneumonia: a prospective observational study

Abstract: Pharmacists play an integral role in antimicrobial stewardship (AS). Some AS programmes employ dedicated pharmacists, sometimes with infectious diseases (ID) training, while others employ ward-based pharmacists. The role and impact of both are under investigation. This study compares the length of stay (LOS) of patients admitted to hospital with community-acquired pneumonia (CAP) after the implementation of an AS programme initially led by a dedicated ID-trained pharmacist, and then transitioned to a ward-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…In a meta-analysis, it was shown that interventions reduced LOS by 1.12 days (Davey et al, 2013). In another study, it was demonstrated that a prospective audit and feedback intervention reduced median LOS in patients with community-acquired pneumonia by nearly 0.5 days (DiDiodato and McAthur, 2017). The overall reduction in LOS was 19.4%.…”
Section: Discussionmentioning
confidence: 98%
“…In a meta-analysis, it was shown that interventions reduced LOS by 1.12 days (Davey et al, 2013). In another study, it was demonstrated that a prospective audit and feedback intervention reduced median LOS in patients with community-acquired pneumonia by nearly 0.5 days (DiDiodato and McAthur, 2017). The overall reduction in LOS was 19.4%.…”
Section: Discussionmentioning
confidence: 98%
“…The acceptability, importance, and implementation of hospital-based AMS programs across different hospital settings is well-described in the literature due to their acknowledged benefits ( Brotherton, 2018 ; Chen et al, 2018 ; Burgess et al, 2019 ; Onorato et al, 2020 ). Numerous developed countries, including the United States, United Kingdom, Australia, and Canada, have implemented AMS programs successfully ( Seo et al, 2016 ; Charani et al, 2017 ; DiDiodato and McAthur, 2017 ; Rautemaa-Richardson et al, 2018 ; Cipko et al, 2020 ); however, its implementation in developing countries is challenging ( Hayat et al, 2020 ). It has been proven that pharmacist-driven AMS is beneficial in reducing the duration of antimicrobial treatment, shortening hospital stays, lowering patient mortality, optimizing antimicrobials use, and limiting the emergence of multidrug-resistant organisms ( Li et al, 2017 ; Parente and Morton, 2018 ; Wang et al, 2019 ; Sadyrbaeva-Dolgova et al, 2020 ; Takito et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 34 35 ] In two studies, prospective audit is used as an intervention to control the antimicrobial cost of treatment. [ 36 37 ] A study being performed in the Tokyo Metropolitan Hospital in Japan using prospective audit intervention to control the resistant Gram-negative bacilli (GNB) infection found a significant ( P < 0.01) fall of carbapenem resistance in Pseudomonas aeruginosa . [ 38 ] In an ID physician-led community hospital AMS program where the ID physician closely monitored the susceptibility and cost patterns of antimicrobial practice showed a remarkable improvement in controlling the AMR and cost within the hospital.…”
Section: R Esultsmentioning
confidence: 99%